Comparison of conventional and reversed phage typing procedures for identification of Listeria spp. - Estela, L A (1993)
Of 225 Listeria isolates evaluated, 199 had the same bacteriophage patterns by both the conventional (A. Audurier, A.G. Taylor, B. Carbonelle, and J. McLaughlin, Clin. Invest. Med. 7:229-232, 1984) and the new, easier to apply, "reversed" (M. J. Loessner, Appl. Environ. Microbiol. 57:882-884, 1991) phage typing procedures, 5 had different phage reactions, and the remaining 21 isolates were untypeable. Thus, the overall typeability rate was 90.7%, and 97.6% of the typeable isolates had the same phage patterns by both procedures.